Plasmacytoid dendritic cells: sensing nucleic acids in viral infection and autoimmunity - Liu, Yong-Jun (Henry Stewart Talks, 2009)
Plasmacytoid dendritic cells (pDCs) are important mediators of antiviral immunity through their ability to produce large amounts of type I interferons (IFNs) on viral infection, This function of pDCs is linked to their expression of Toll-like receptor 7 (TLR7) and TLR9, which sense viral nucleic acids within the early endosomes, Exclusion of self nucleic acids from TLR-containing early endosomes normally prevents pDC responses to them, In some autoimmune diseases, self nucleic acids can be modified by host factors and gain entrance to pDC endosomes, where they activate TLR signaling, Several pDC receptors negatively regulate type I IFN responses by pDCs during viral infection and for normal homeostasis